Ensayo bibliografico sobre el antropologo Manuel Marzal - Sara Lafosse, Mercedes Giesecke (2005)
This sketch describes the intelectual and religious journey of an anthropologist committed to the investigation of the Andean world. The autor present his bibliographical production and his insitutional work.